Enhancing accuracy through an efficient ensemble of geographically fine-tuned positional encoder graph neural networks - Seabra, Vívia de Alencar (2024)
Dissertação (mestrado) — Universidade de Brasília, Instituto de Ciências Exatas, Departamento de Estatística, 2024.